The role of family health climate in physical activity and sedentary behaviour in primary care patients with diabetes – a cross-sectional study - Amelia Ahmad Hatib; Hui Li Koh; Sai Zhen Sim (BMC Primary Care)
Abstract Background The shared perceptions and cognitions of a family toward health such as exercise are termed the family health climate (FHC), and they may influence individual physical activity levels. This study aimed to examine the associations between the FHC and physical activity and sedentary behaviour in adult patients with diabetes while accounting for sociodemographic factors and self-determined motivation. Methods This cross-sectional study was conducted at a polyclinic in Singapore. The participants completed anonymized, self-administered questionnaires that collected data on sociodemographic variables, family health climate for physical activity (FHC-PA), self-reported physical activity and sedentary behaviour (Global Physical Activity Questionnaire), and self-determined motivation (Behavioural Regulation in Exercise Questionnaire‑2). The data were analysed descriptively, and logistic regression was performed to examine the sociodemographic, FHC and motivational covariates of physical activity and sedentary behaviour. Results A total of 345 participants were included in the analysis. The majority were male (60.3%), Chinese (67.5%), and working (72.8%). The mean age was 61.56 (SD 10.71) years. A minority of the participants had sufficient physical activity (41.2%), and most were sedentary (62%). After we adjusted for sociodemographic factors and self-determined motivation, the FHC-PA score and its subdomains were not associated with physical activity levels (p > 0.05) or sedentary behaviour (p > 0.05). Those with higher identified regulation scores had higher odds of being sufficiently active, whereas those with higher external regulation scores, from larger households and who were employed had lower odds of sufficient physical activity. Higher degrees of autonomous motivation were associated with reduced sedentary behaviour, whereas being employed was associated with increased sedentary behaviour. Conclusion The FHC-PA, in the presence of self-determined motivation and sociodemographic factors, was not associated with the individual physical activity levels of adults with diabetes. Further studies can be conducted to determine whether it plays a mediating role. As identified regulation was associated with both physical activity and sedentary behaviour, interventions can be mapped to target this motivational domain.